Prioritizing dams for removal to advance restoration and conservation efforts in the western United States. Issue 5 (25th November 2021) - Guetz, Katie; Joyal, Taylor; Dickson, Brett; Perry, Denielle
Abstract : Dams are socio‐ecological structures fundamentally serving human population growth and economic development. Yet, dams have significantly reduced landscape connectivity, altered hydrologic and geomorphic dynamics, and are a leading cause of freshwater biodiversity decline. As dams age and are no longer used for their original intended purpose, they increasingly threaten both humans and ecosystems. Consequently, dam removal is an increasingly accepted strategy to restore river systems across the United States; since the 1970s, more than 1, 400 dams have been removed. As the removal trend continues, important decisions must be made regarding which dams are still ecologically and economically viable and which are optimal for removal to facilitate restoration and subsequent protection. Therefore, it is critical to prioritize dams for removal where rivers, freshwater resources, and ecosystem services will benefit most. To that end, this study uses geospatial analysis and a multi‐criteria decision framework to evaluate dams suitable for removal in the western United States in watersheds with existing conservation priorities, and to examine watershed dynamics in which they are situated. Results reveal 24 top‐ranked dams no longer performing essential ecological and social functions as optimal sites for removal to restore waterways. Of these top‐ranked dams, four are already in the planning process for removal, indicating the model is performing as intended. These results are critical for managers and policymakers to understand where dam removals could enhance overall riverine connectivity and where river restoration could result in subsequent protection of newly free‐flowing river segments in the National Wild and Scenic Rivers System.